10 Pilonidal Disease (Gordon and Nivatvongs’ Principles and Practice of Surgery for the Colon, Rectum, and Anus, 2019)
The proximity of pilonidal disease to the anus has prompted the referral of many patients with this problem to colon and rectal surgeons. Pilonidal sinus is a chronic subcutaneous abscess in the natal cleft, which spontaneously drains through the openings. It is not a “cyst,” as frequently referred to. This chapter discusses the pathophysiology, clinical presentation, diagnosis, and treatment of pilonidal disease.
Keywords: pilonidal disease; sinus; complex disease; recurrent disease; clinical presentation; diagnosis; treatment